DECENTRALIZED AUTONOMOUS ORGANIZATIONS: UNLOCKING THE FULL POTENTIAL OF BLOCKCHAIN TECHNOLOGY FOR THE REAL PHYSICAL WORLD BY EXPLORING SELF-ORGANIZING AND SELF-REGULATING DECENTRALIZAD SYSTEMS BY APPLYING SMART CONTRACTS AND FIRST ATTEMPTS OF APPLYING AI - Hannemann, Jan-Gero Alexander (International Journal of Law in Changing World, 2023)
This paper explores the potential of DAOs (Decentralized Autonomous Organizations) built on blockchain technology, which are expected to revolutionize our computing and transaction infrastructures. By combining Blockchain technology or DAGs (directed acyclic graphs)with Artificial Intelligence (AI), self-operating electronic systems could be created, making them the elementary foundations for processing, coordinating, incentivizing, and financing IoT applications and the basis of the next generation of robotics. This paper will focus on the legal classification of DAOs, with an emphasis on the mechanisms of raising capital through ICOs and NFTs as alternative financing options for easier access to capital. The potential of linking DAOs and AI is also briefly addressed. Corporate law must keep pace with this rapid change, and the question arises whether it is "sufficiently flexible to make room for the new technical possibilities" and to cover completely "new forms of organization" based on software code that may be inadequately reflected in existing regulations. Overall, this paper highlights the potential of DAOs and their impact on the future of business models, organizational structures, and financing options.